2013
DOI: 10.1007/s12010-013-0295-y
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment for Simultaneous Production of Total Lipids and Fermentable Sugars from Marine Alga, Chlorella sp.

Abstract: The goal of this study was to determine the optimal pretreatment process for the extraction of lipids and reducing sugars to facilitate the simultaneous production of biodiesel and bioethanol from the marine microalga Chorella sp. With a single pretreatment process, the optimal ultrasonication pretreatment process was 10 min at 47 KHz, and extraction yields of 6.5 and 7.1 (percentage, w/w) of the lipids and reducing sugars, respectively, were obtained. The optimal microwave pretreatment process was 10 min at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Ma et al, 2014 [14] reported the increase in extraction yield resulting from microwaves was equal to the increase in yield from ultrasonication, which is consistent with this study. In prior studies, the increase in yield ranged from 30% [10] to 120% [8] for ultrasonication and from 40% [14] to 600% [15] for microwaves. These studies used different solvent ratios, that may not have been as ideal as those prescribed by Bligh and Dyer, and the benefits of pretreatment may have been greater for less efficient solvents.…”
Section: Impact Of Pretreatment On Solvent Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ma et al, 2014 [14] reported the increase in extraction yield resulting from microwaves was equal to the increase in yield from ultrasonication, which is consistent with this study. In prior studies, the increase in yield ranged from 30% [10] to 120% [8] for ultrasonication and from 40% [14] to 600% [15] for microwaves. These studies used different solvent ratios, that may not have been as ideal as those prescribed by Bligh and Dyer, and the benefits of pretreatment may have been greater for less efficient solvents.…”
Section: Impact Of Pretreatment On Solvent Extractionmentioning
confidence: 99%
“…Therefore, the TIs used above were selected based on results reported in prior studies for electroporation [22], ultrasonication [10,12], and microwave [14,15].…”
Section: Pretreatment Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…cells ranges from 20% to 26% in autotrophic conditions, which is the amount of sugar required for the production of bio-ethanol. [5] Therefore, we believe that due to their lipid and sugar content, these cells could be used for the co-production of biofuels. [5] However, marine microalgae have a two-layered cell wall consisting of outer and inner cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Therefore, we believe that due to their lipid and sugar content, these cells could be used for the co-production of biofuels. [5] However, marine microalgae have a two-layered cell wall consisting of outer and inner cell walls. Of these two, the outer cell wall has a trilaminar structure of mixed multilayers that include cellulose.…”
Section: Introductionmentioning
confidence: 99%